Emergent Topics and Development of Studies on International Students in China 近二十年来华留学生研究的热点与演进趋势: A Visualized Analysis of CSSCI Journals from 1998-2018 基于CSSCI的可视化分析 - Zhang, Xiufeng; Yang, Hengwen (Journal of International Students, 2020)
The present study analyses the research articles which focused on international students in China between 1998 and 2018. The data were retrieved from the Chinese Social Sciences Citation Index (CSSCI) database and visualized using Citespace 5.0.R7. This paper analyses the key authors, research institutes, disciplines, publishing agency, and co-citation keywords to trace emergent topics and new trends of the research on international students in China. The findings facilitate an in-depth understanding of the research hotspots over the past two decades. This paper has implications for further research on international students in China. 借助Citespace5.0.R7 分析工具，对1998-2018年间CSSCI数据库收录的742篇有关来华留学生研究论文进行可视化分析。通过对二十年来华留学生研究所涉及的主要作者、研究机构、研究学科分布、来源出版物和共被引关键词进行可视化分析，以追踪本领域内总体动态，研究热点和发展趋势。研究成果有助于理清近二十年来华留学生研究领域的动态发展和未来趋势，为我国来华留学生相关研究和高等教育国际化提供参考。